Biological and physical fitness adaptations in soccer players after jump training: a systematic scoping review - Kumar Thapa, Rohit; Gracia-Carrillo, Exal; Sortwell, Andrew; Byrne, Paul J.; Afonso, Jose; Ramirez-Campillo, Rodrigo (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. To conduct a systematic scoping review assessing the effects of jump training in soccer players physical fitness. Methods. Included studies incorporated: (i) soccer players; (ii) jump-training interventions; and (iii) outcomes related to physical fitness (e.g. endurance). Selection was not based on comparator groups and/or study designs. PubMed, Web of Science, and Scopus databases were searched for documents. One author led the process, and a second author independently verified the process. The type of outcome measure determined studies aggrupation [e.g. vertical jump (e.g. height; contact time)], with a narrative synthesis accompanied by data summaries (e.g. percentage).Results. Included studies involved males (adults k = 25; youths k = 52) and females (adults k = 8; youths k = 3). Non-randomised interventions (single-arm and multi-arm) comprised ~40% of the studies, with durations between 3–96 weeks, and improvements in 1 outcome, including body composition, stiffness, electromyographic activity, potential injury risk factors, kicking velocity, repeated sprint ability, linear sprinting, endurance, balance, maximal strength, and jump performance. However, only 10-13 participants were involved in jump training groups. Further, false significant results and publication bias in favour of studies with significant findings are potentially common issues in the available literature.Conclusions. Jump training may improve physical fitness in soccer players. However, methodological issues (e.g. non-randomised-controlled studies) and evidence gaps (e.g. fewer female studies) were noted. More and better-designed jump training studies on soccer participants are advised before robust recommendations regarding optimal jump training regimens can be made.
Keywords: human physical conditioning; athletic performance; football; sports; plyometric exercises; resistance training